Menelisik Penerapan Digital Entrepreneurship Pada Small Medium Enterprise (Fakultas Ekonomi Universitas Gresik, 2023)
Preparing MSME to develop businesses through digital entrepreneurship is important to accelerate the digitization and MSME’s sustainable business. This study aims to discuss the implementation of digital entrepreneurship in MSMEs and explore the factors that can influence the implementation of digital entrepreneurship. This research is a qualitative research. This study involved ten micro and small business activists in the Bali region. Semi structured interviews were used as a data collection technique. The findings indicated that seven out of ten MSMEs stated that they do not clearly understand how to use technology into their business, some of them consider it is a complexity. Some even think it is not necessary to involve technology in their business, they show some concern. Then the factors that influence the application of digital entrepreneurship appear, things that are conveyed the most are courage, they learn about the market trend, interested use technological innovation, never stop learning and never give up. The contribution of this research is found in the factors that influence the application of digital entrepreneurship as a MSME business strategy. This research offers a comprehensive model to understand the factors that influence application of digital entrepreneurship to MSMEs. This model can be used as a reference for further research to develop survey instruments in an effort to obtain empirical evidence which can be generalized about the factors that influence the application of digital entrepreneurship in MSMEs. In addition, this research can also be used as a reference source for formulating the right strategy in digitizing MSMEs